Pengembangan Lembar Kerja Siswa Elektronik (E-LKPD) Fisika Berbasis Problem Based Learning (PBL) untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik Kelas X - Nisrina Hasna Mustofa; Pujianto; Jumadi (Jurnal Penelitian Pendidikan IPA, 2026)
Critical thinking skills are essential in 21st-century education. However, physics learning in schools still relies on conventional teaching materials and limited instructional approaches, resulting in students' low critical thinking skills. Therefore, this study aimed to develop a Problem-Based Learning (PBL)-based Physics Electronic Student Worksheet (E-LKPD) and examine its feasibility and effectiveness in improving students' critical thinking skills. This research employed a Research and Development (R&D) approach using the Four-D (4-D) development model. The effectiveness of the developed E-LKPD was evaluated using a pretest–posttest control group design. Data were collected through interviews, observations, questionnaires, tests, and documentation. The results showed that the developed E-LKPD was highly feasible based on expert validation, practical based on students' responses, and effective in improving students' critical thinking skills. The experimental class achieved a higher N-Gain score (0.364, medium category) than the control class (0.265, low category). These findings indicate that integrating PBL into interactive digital worksheets supports student-centered learning and promotes students' critical thinking skills. Therefore, the developed PBL-based Physics E-LKPD can be used as an effective digital teaching material for improving students' critical thinking skills.